2016
DOI: 10.4149/neo_2016_518
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in urine supernatant as potential non-invasive markers for bladder cancer detection

Abstract: Urinary bladder carcinoma contributes to 4% of newly diagnosed oncological diseases in the Czech Republic. Biomarkers for its early non-invasive detection are therefore highly desirable. Urine seems to be an ideal source of such biomarkers due to the content of cell-free nucleic acids, especially microRNAs (miRNAs).To find potential biomarkers among miRNAs in urine supernatant, we examined in total 109 individuals (36 controls and 73 bladder cancer patients) in three phases. In the first - discovery - phase, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 33 publications
1
34
1
3
Order By: Relevance
“…In addition to BCA detection, our DxScore enabled also to distinguish between NMIBC and MIBC and low‐grade and high‐grade form of NMIBC and significantly decreased in the urinary samples collected after surgery in disease‐free patients compared to pre‐operative samples. When compared to previous studies , our study is performed on the larger cohort of well‐defined patients with BCA and healthy controls, showing more promising analytical characteristics of cell‐free urinary miRNAs in BCA than described before.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to BCA detection, our DxScore enabled also to distinguish between NMIBC and MIBC and low‐grade and high‐grade form of NMIBC and significantly decreased in the urinary samples collected after surgery in disease‐free patients compared to pre‐operative samples. When compared to previous studies , our study is performed on the larger cohort of well‐defined patients with BCA and healthy controls, showing more promising analytical characteristics of cell‐free urinary miRNAs in BCA than described before.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, various molecular and biological markers, such as survivin, interleukins, microRNAs, have also been reviewed (4,5). However, there are no clinically definitive markers for NMIBC, as tumor growth, invasion, metastasis and recurrence are regulated by complex underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In line with let-7c tumorsuppressor role, our analysis of the cluster expression levels in HG-NMIBC patient's tissue showed that let-7c, as well as miR-99a and miR-125b, were highly downregulated compared to normal tissue samples. In urine, let-7c, as well as the other let-7c cluster members, miR-99a and miR-125b has been found down-regulated in BC versus HC [11,22,23]. In the current study, we investigated the potential value of urinary let-7c cluster as noninvasive diagnostic/prognostic biomarker of HG-NMIBC patients.…”
Section: Discussionmentioning
confidence: 96%